"I made a pact with God, with nature, and with myself": exploring deep agroecology. Issue 2 (7th February 2016) - Botelho, Maria Izabel Vieira; Cardoso, Irene Maria; Otsuki, Kei
ABSTRACT: This article reports on the consequences of agroecology for smallholders' personal and social world in a coffee-growing region of Zona da Mata in Brazil. Agroecology is usually considered a technically and politically rational approach for smallholders to counter large-scale agribusinesses. However, while practicing agroecology, smallholders come to reinforce their religious views and rearticulate personal relationships with the natural and social environment. This article argues that we need to pay more attention to such "deep" experiences that are caused by agroecology and to clarify the relevant policy implications. Some aspects of studies on indigenous cosmology in Latin America and deep ecology may become useful.